The reality of the international rankings for the quality of Iraqi universities (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The international ranking of the quality of universities is one of the important topics that have taken a great deal of attention that is related to the scientific status at the local, regional and international levels.Quality means a set of characteristics and features of a product or service related to its ability to meet   a specific need by making the product or service   suitable for use.         The quality of education represents the degree that meets a set of educational characteristics specified in accordance with the standards of institutional accreditation of educational indicators in achieving the quality of the educational product, and the educational institution usually seeks to reach them. Accordingly, the research is concerned with presenting the types of international rankings for the quality of universities and identifying the ranking of Iraqi universities according to the international quality ratings, and then presenting the determinants that hinder the entry of Iraqi universities in the international rankings for the quality of higher education and coming up with a number of conclusions and recommendations for the research.